Study protocol for a natural experiment in a lower socioeconomic area to examine the health-related effects of refurbishment to parks including built-shade (ShadePlus). Issue 2 (22nd February 2017) - Dobbinson, S J; Veitch, J; Salmon, J; Wakefield, M; Staiger, P K; MacInnis, R J; Simmons, J
Abstract : Introduction: Parks in disadvantaged suburbs often have low quality and few amenities, which is likely to result in them being underutilised for recreation and physical activity. Refurbishment of parks, including shade, walking paths and other amenities, may have broad health-related benefits. Methods and analysis: The study design, methods and planned analyses for a natural experiment examining the effects of refurbishments including built-shade added to parks in disadvantaged outer suburbs of Melbourne are described. Three intervention parks and three comparison parks matched for equivalence of park and neighbourhood characteristics were selected. Using mixed methods, the outcomes will be assessed during three consecutive spring–summer periods (T1: 2013–2014; T2: 2014–2015: T3: 2015–2016). Primary outcomes included: observed park use, physical activity and shade use. Self-reported social connectedness, community engagement and psychological well-being were assessed as secondary outcomes. Ethics and dissemination: This study was approved by Cancer Council Victoria's Human Research Ethics Committee. Studies such as ShadePlus can improve understanding of the broader effects of park refurbishments (including physical activity levels and sun protection behaviours, as well as social connectedness and psychological well-being). The study findings will be disseminated through established urban planning and parks and recreation networks, peer review publications and conference presentations.